(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In this article, the author pays special attention to reducing the risk of inflammation associated with cardiovascular diseases by treating aggressive periodontitis. It should be noted that one of the pressing problems of modern dentistry is the study of the negative systemic effect of long-term inflammatory diseases of the oral cavity, especially with regard to periodontal disease, since, according to WHO statistics, the world population over 45 years of age has this type disease and its consequences.